2021
DOI: 10.1186/s12884-021-03621-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor gene polymorphisms with gestational diabetes mellitus-a case control study in Wuhan, China

Abstract: Background Gestational diabetes mellitus (GDM) increased risk of perinatal complications for both the women and the fetuses. The association between the vitamin D receptor (VDR) gene polymorphism and GDM has not been thoroughly investigated in Chinese pregnant women. Therefore, we aimed to determine whether VDR gene single nucleotide polymorphisms (SNPs) rs154410, rs7975232, rs731236, rs2228570 and rs739837 contribute to GDM risk in Wuhan, China. Moreover, we aimed to explore their combined eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In some epidemiologic studies, the shorter FokI VDR allelic variation has been associated with a host of adverse disease outcomes (16,17), including increased risk to MetS in adults (2,3,15,16,18,19). Furthermore, increased susceptibility to GDM from expectant mothers having the FokI variant were observed among expectant mothers coming from Turkey (20) and Iran (21), but not Chinese (22) and Saudi Arabians (23), which means that FokI may confer susceptibility only to select populations (24). To date, there is scarcity of evidence linking MetS and FokI VDR SNPs in pregnant women, more so in understudied ethnic groups such as Saudi Arabians.…”
Section: Introductionmentioning
confidence: 99%
“…In some epidemiologic studies, the shorter FokI VDR allelic variation has been associated with a host of adverse disease outcomes (16,17), including increased risk to MetS in adults (2,3,15,16,18,19). Furthermore, increased susceptibility to GDM from expectant mothers having the FokI variant were observed among expectant mothers coming from Turkey (20) and Iran (21), but not Chinese (22) and Saudi Arabians (23), which means that FokI may confer susceptibility only to select populations (24). To date, there is scarcity of evidence linking MetS and FokI VDR SNPs in pregnant women, more so in understudied ethnic groups such as Saudi Arabians.…”
Section: Introductionmentioning
confidence: 99%
“…It has often been indicated that some VDR gene variants could be associated with an increased risk of chronic hypertension [ 49 , 50 ]. Thus far, several publications have analyzed the relationship of VDR gene polymorphisms with the occurrence of certain complications in pregnancy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results were corroborated by the research performed by Wang et al, in which the authors found associations of VDR BsmI and FokI variants with hypertension risk in Japanese men [ 49 ]. Additionally, a meta-analysis performed by Zhu et al revealed a significant correlation between the VDR BsmI variant and susceptibility to hypertension [ 50 ]. The very exciting result in our study was the observation that 3-marker haplotype CTA ( TaqI, ApaI, BsmI ) was associated with significantly higher systolic ( p = 0.0075) and diastolic ( p = 0.0072) blood pressure values.…”
Section: Discussionmentioning
confidence: 99%
“…The method of data collection was reported in previous article. 25 The study protocol was approved by the institutional review board of Wuhan University of Science and Technology and was performed in accordance with the Declaration of Helsinki. All subjects provided informed consents for participation.…”
Section: Methodsmentioning
confidence: 99%
“…The method of sample collection was also reported in the previous article. 25 The aforementioned five SNPs were genotyped on the Sequenom MassARRAY platform (Sequenom Inc., San Diego, CA, USA). For quality control: (i) case and control samples were mixed on each plate; (ii) genotyping was performed blinded to case or control status; (iii) two water controls were used in each plate as blank controls; (iv) 5% of the samples were randomly selected for repeated genotyping, as blind duplicates, and the reproducibility was 100%.…”
Section: Methodsmentioning
confidence: 99%